NILAI PENDIDIKAN AKHLAK PERSPEKTIF IMAM NAWAWI: (Studi Kitab At-Tibyan Fi Adabi Hamalah Al-Qur’an Karya Imam Nawawi) - Abdul Rohman; Rahmida Putri; Ahmad Hanany (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2021)
This article examines the value of moral education in the book At-Tibyan Fi Adabi Hamalah Al-Qur’an by Imam Nawawi. This study is included in the category of library research. The study method used is descriptive analytical. The primary data in this study comes from the book At-Tibyan Fi Adabi Hamalah Al-Qur’an. The results of the research on the value of moral education contained in the book At-Tibyan Fi Adabi Hamalah Al-Qur’an include intending to only expect the pleasure of Allah, getting used to commendable morals, not expecting worldly results, studying with competent teachers, being polite, being polite and joining with others. Ladies and gentlemen, glorify people who memorize the Koran and are forbidden to hurt them, protect and respect the Koran, face the Qibla, clean the mouth, in a state of purity. The value of moral education offered by Imam Nawawi is the value of moral education that can be actualized in Indonesian education as an answer to the decline in morals in the current era of disruption.